2007
DOI: 10.1007/s10534-007-9118-3
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxicity and mutagenicity of iron and copper in mice

Abstract: The toxicity of trace metals is still incompletely understood. We have previously shown that a single oral dose of iron or copper induces genotoxic effects in mice in vivo, as detected by single cell gel electrophoresis (comet assay). Here, we report the effect of these metals on subchronic exposure. Mice were gavaged for six consecutive days with either water, 33.2 mg/kg iron, or 8.5 mg/kg copper. On the 7th day, the neutral and alkaline comet assays in whole blood and the bone marrow micronucleus (MN) test w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0
7

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(33 citation statements)
references
References 55 publications
3
23
0
7
Order By: Relevance
“…Consistent with these results, Prá et al (2008) noted that ferrous sulfate induces DNA damage in peripheral blood cells and mouse bone marrow through an increase in the frequency of micronuclei. Clastogenic effects were also induced by ferrous sulfate in a micronucleus assay (Premkumar and Bowlus, 2003) in mouse bone marrow cells.…”
Section: Discussionsupporting
confidence: 77%
“…Consistent with these results, Prá et al (2008) noted that ferrous sulfate induces DNA damage in peripheral blood cells and mouse bone marrow through an increase in the frequency of micronuclei. Clastogenic effects were also induced by ferrous sulfate in a micronucleus assay (Premkumar and Bowlus, 2003) in mouse bone marrow cells.…”
Section: Discussionsupporting
confidence: 77%
“…Bulky DNA lesions are associated with chromosome breaks and micronuclei frequency (Prá et al 2008). The increase in bone marrow micronuclei frequency in the group of rats treated with sucrose can be related to the capacity of sucrose to induce mutations, as previously observed in the colon of rats treated with sucrose-rich diet (Dragsted et al 2002).…”
Section: Discussionmentioning
confidence: 56%
“…At the end of the experiment, the femurs of the animals were removed and slides were prepared as described by Prá et al (2008). Briefly, bone marrow was mixed with fetal calf serum and smears were prepared with this mixture.…”
Section: Test Of Micronucleus In Bone Marrow Erythrocytesmentioning
confidence: 99%
“…An enrichment of aneuploid events in copper may well be due to selection for aneuploidy rather than an increased mutation rate, consistent with the frequent occurrence of additional copies of chrVIII, bearing CUP1. Nevertheless, previous studies with mice have found copper to be mutagenic, using a micronuclei assay that is sensitive to errors in chromosome segregation during mitosis (Prá et al 2008). We thus consider it plausible that the high frequency of aneuploidy observed in this study may have been directly due to copper exposure.…”
Section: Mutagenic Effects Of Coppermentioning
confidence: 52%